The Argumentative Mechanisms in the Poem of Amr ibn Ma'adi Yakrib’s Laysa Al-Jamalu Bi-Mi'zarin - Al-Qahtani, Madhkar Bin Nasser (Arts for Linguistic & Literary Studies, 2025)
يتناول هذا البحث قصيدة عمرو بن معدي كرب الدالية (ليس الجمال بمئزر)؛ بغرض البحث عن آليات الحجاج التي استعملها الشاعر فيها؛ للتأثير في المتلقين، وإقناعهم بأفكاره ورؤاه، معتمدًا على المنهج الحجاجي التداولي، وجاء في مقدمة وتمهيد، ثم ثلاثة مباحث، ونتائج، تناول التمهيد الإطار النظري للحجاج، ونص القصيدة، ولمحة عن موضوع القصيدة (الجمال). وناقش المبحث الأول: آليات الحجاج اللغوي. وتناول المبحث الثاني: آليات الحجاج البلاغي. وتناول المبحث الثالث: آليات الحجاج شبه المنطقي. وكان من أهم نتائج البحث: أن آليات الحجاج اللغوي هي الآليات المسيطرة على النص؛ لأن اللغة بطبيعتها وسيلة حجاجية في الأصل؛ إذ إن من أهدافها إقناع المتلقي والتأثير فيه. وقد تعددت آليات الحجاج اللغوي لدى عمرو بن معدي كرب، وتراوحت بين الكثرة والقلة من حيث الورود، وقد كانت صيغ المبالغة هي الأقل ورودا؛ ولعل ذلك يرجع إلى اهتمام الشاعر بتصوير الواقع كما هو دون مبالغة، فقد كانت شجاعته وبأسه وصبره من الشهرة بمكان؛ ولذا لم ترد هذه الصيغ لديه كثيرًا. واستعان الشاعر بالآليات البلاغية في المحاججة بها، وتمثلت هذه الآليات في التشبيه والاستعارة؛ مما أكسب الخطاب بعدا حجاجيا، مع المحافظة على بُعده الشاعري والجمالي. This study explores the argumentative mechanisms in Amr ibn Ma'adi Yakrib's poem Laysa Al-Jamalu Bi-Mi'zarin ‘Beauty is Not in a Loincloth’, focusing on how the poet persuades and influences his audience. Using the argumentative communicative approach, the research is structured into an introduction, a preface, three sections, and a conclusion. The preface outlines the theoretical framework of argumentation, the poem’s text, and its central theme of beauty. The first section examines linguistic argumentative mechanisms, revealing that language serves as the primary tool for persuasion, as its inherent purpose is to convince and influence. These mechanisms vary in frequency, with forms of exaggeration being the least common. This may reflect the poet's preference for portraying reality authentically, consistent with his reputation for courage, strength, and patience. The second section focuses on rhetorical mechanisms, highlighting the use of simile and metaphor, which add both argumentative depth and aesthetic value to the poem. The third section analyzes quasi-logical mechanisms, emphasizing their role in reinforcing the poet’s arguments. The study concludes that linguistic mechanisms dominate the poem, with rhetorical tools complementing them to enhance its persuasive and poetic dimensions.